2020
DOI: 10.1038/s41598-020-63362-4
|View full text |Cite
|
Sign up to set email alerts
|

Construction of higher-order cellular microstructures by a self-wrapping co-culture strategy using a redox-responsive hydrogel

Abstract: In this report, a strategy for constructing three-dimensional (3D) cellular architectures comprising viable cells is presented. the strategy uses a redox-responsive hydrogel that degrades under mild reductive conditions, and a confluent monolayer of cells (i.e., cell sheet) cultured on the hydrogel surface peels off and self-folds to wrap other cells. As a proof-of-concept, the self-folding of fibroblast cell sheet was triggered by immersion in aqueous cysteine, and this folding process was controlled by the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 75 publications
(99 reference statements)
0
11
0
Order By: Relevance
“…[71][72][73] Cell sheets co-cultured with endothelial cells are highly vascularized to offer sufficient oxygen and nutrients and show high transplantation efficiency. 74,75 The results indicate the critical role of vascularization in successful transplantation of highly functional multilayered and 3D cell sheets.…”
Section: Vascularized Cell Sheetmentioning
confidence: 88%
“…[71][72][73] Cell sheets co-cultured with endothelial cells are highly vascularized to offer sufficient oxygen and nutrients and show high transplantation efficiency. 74,75 The results indicate the critical role of vascularization in successful transplantation of highly functional multilayered and 3D cell sheets.…”
Section: Vascularized Cell Sheetmentioning
confidence: 88%
“…Reproduced with permission. [ 215 ] Copyright 2020, Springer Nature. g–j) Cell invasion of MDA‐MB‐231 in GelMA and Col I hydrogels.…”
Section: Engineering the Tme Using Protein‐based Hydrogelsmentioning
confidence: 99%
“…Moreover, these MTs improved the cellular function of hepatocytes when compared with cellular aggregates without the cell layer coating it. [ 215 ]…”
Section: Engineering the Tme Using Protein‐based Hydrogelsmentioning
confidence: 99%
“…However, there still exist some problems associated with the incomplete adherence of the spheroid on the substrate and difficulties in regulating the cellular movement and cell density on the outer membrane of the encapsulated cells [89]. Ramadhan et al, (2020) suggested a redox-responsive hydrogel that enables self-wrapping co-culture [39]. Its mechanism involves decomposition of hydrogels under mild reductive microenvironments, and the peeling-off of a monolayer of cells cultured on a redox-responsive hydrogel surface that self-folds to wrap other cell lines.…”
Section: Hydrogel-based Platformsmentioning
confidence: 99%